2019
DOI: 10.1186/s12934-019-1243-5
|View full text |Cite
|
Sign up to set email alerts
|

Redesigning the Aspergillus nidulans xylanase regulatory pathway to enhance cellulase production with xylose as the carbon and inducer source

Abstract: BackgroundBiomass contains cellulose (C6-sugars), hemicellulose (C5-sugars) and lignin. Biomass ranks amongst the most abundant hydrocarbon resources on earth. However, biomass is recalcitrant to enzymatic digestion by cellulases. Physicochemical pretreatment methods make cellulose accessible but partially destroy hemicellulose, producing a C5-sugar-rich liquor. Typically, digestion of pretreated LCB is performed with commercial cellulase preparations, but C5-sugars could in principle be used for “on site” pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…Based on bioinformatic analyses of the fungal genomes, it has been revealed that fungi display enormous potential to yield significantly more natural products than what has been discovered to date [2]. As a class of common filamentous fungi, species of the genus Aspergillus, such as Aspergillus niger, Aspergillus oryzae, and Aspergillus terreus, have long been regarded as cell factories because of their abilities to survive in varied pH (2)(3)(4)(5)(6)(7)(8)(9)(10)(11), a wide temperature range (10-50 • C), and salinity ranges (0-34%), as well as in the other extreme stressful conditions [3]. Therefore, until now, Aspergillus species have been increasingly applied to biosynthesize enzymes, food additives, pharmaceuticals, and so on [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on bioinformatic analyses of the fungal genomes, it has been revealed that fungi display enormous potential to yield significantly more natural products than what has been discovered to date [2]. As a class of common filamentous fungi, species of the genus Aspergillus, such as Aspergillus niger, Aspergillus oryzae, and Aspergillus terreus, have long been regarded as cell factories because of their abilities to survive in varied pH (2)(3)(4)(5)(6)(7)(8)(9)(10)(11), a wide temperature range (10-50 • C), and salinity ranges (0-34%), as well as in the other extreme stressful conditions [3]. Therefore, until now, Aspergillus species have been increasingly applied to biosynthesize enzymes, food additives, pharmaceuticals, and so on [4].…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in synthetic biology have enabled the biosynthesis of various secondary metabolites in A. nidulans, including benzylpenicillin [7], m-cresol [8], and asperniduglene A1 [9]. The production of primary metabolites in A. nidulans is basically limited to those synthesized by certain enzymes including carbohydrate-active enzymes [10], cellulase [11], and lignocellulose-modifying enzymes [12], while other primary metabolites, such as organic acids, have rarely been reported, which somewhat limits the expansion of the application spectrum of A. nidulans.…”
Section: Introductionmentioning
confidence: 99%